The Relationship Between Stress Levels, Eating Patterns, and Caffeine Consumption and Gastritis Symptoms Among Adolescents in Karawang - Zahrah, Hanifah; Elvandari, Milliyantri; Andriani, Eka (PROMOTOR, 2025)
Adolescence is a transitional stage that makes individuals vulnerable to health issues such as gastritis, a common digestive disorder often linked to stress, poor eating patterns, and caffeine intake. This study aimed to analyze the relationship between stress levels, eating patterns, and caffeine consumption with gastritis symptoms among adolescents at SMAN 2 Telukjambe Timur, Karawang. Using a cross-sectional design, data were collected from 92 students through validated questionnaires and analyzed with the Spearman correlation test. The results showed no significant relationship between stress levels and gastritis symptoms (p = 0.074) or caffeine consumption and gastritis symptoms (p = 0.102). However, there was a significant relationship between eating patterns (type, frequency, and timing) and gastritis symptoms (p = 0.001 and p = 0.002). This indicates that healthy and regular eating habits play a crucial role in preventing gastritis among adolescents.